2008
DOI: 10.1002/ajh.21247
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation for Epstein–Barr virus‐associated T/natural killer‐cell lymphoproliferative disease in Japan

Abstract: Epstein-Barr virus (EBV)-associated T/NK-cell lymphoproliferative disease (LPD) has been linked to several different disorders. Its prognosis is generally poor and a treatment strategy has yet to be established. There are reports, however, that hematopoietic stem cell transplantation (HSCT) can cure this disease. To clarify the current situation regarding allogeneic hematopoietic stem cell transplantation (allo-HSCT) for EBV-associated T/NK-LPD, a nationwide survey was performed in Japan. Data for 74 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…Patients with CAEBV have a higher risk of transplantation-related complications. 41,48 Recently, Kawa et al reported excellent outcome of HSCT with reduced-intensity conditioning. 40 Although the superiority of reduced-intensity conditioning over myeloablative conditioning did not reach statistical significance in that study, it appears that a reduced-intensity regimen is sufficient to prevent transplantation-related deaths.…”
Section: Ebv-associated T/nk-lpd 683mentioning
confidence: 99%
“…Patients with CAEBV have a higher risk of transplantation-related complications. 41,48 Recently, Kawa et al reported excellent outcome of HSCT with reduced-intensity conditioning. 40 Although the superiority of reduced-intensity conditioning over myeloablative conditioning did not reach statistical significance in that study, it appears that a reduced-intensity regimen is sufficient to prevent transplantation-related deaths.…”
Section: Ebv-associated T/nk-lpd 683mentioning
confidence: 99%
“…In contrast, allogeneic HSCT has been successful in several cases reported from Japan. [12][13][14] We report our experience with 19 patients with CAEBV. Sixteen consecutive patients were followed at the National Institutes of Health (NIH) Clinical Center during the past 28 years, and 3 patients were seen at Baylor College of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients are treated with antiviral agents (acyclovir and ganciclovir), cytokines (Interferon-α and Interleukin-2), and chemotherapy (corticosteroids, etoposide, and cyclosporine). Recently, promising results have been obtained with autologous EBV-specific cytotoxic T cell therapy and hematopoietic cell transplantation (Savoldo et al 2002;Gotoh et al 2008;Sato et al 2008). The chemotherapy reduced the EBV DNA levels of this patient.…”
Section: Discussionmentioning
confidence: 93%